Synthesis, crystal structure, and DFT study of 1-cyclopropyl-3-(3-((1-(2-methoxyphenyl)-5-oxo-[1, 2, 4]triazolo[4, 3-a]quinazolin-4(5H)-yl)methyl)phenylurea. Issue 1 (24th March 2023) - Yao, Lihong; Wu, Qingmei; Chen, Yumei; Ye, Wenjun; Wang, Sisi; Jia, Yihe; Zhou, Zhixu; Zhao, Chunshen
Abstract: A new triazoline-quinazolinone compound, 1-cyclopropyl-3-(3-((1-(2- methoxyphenyl)-5-oxo-[1, 2, 4]triazolo[4, 3-a]quinazoline-4(5H)-yl)methyl)phenylurea, was attained by nine steps and selected the method of inverse synthetic analysis. Meanwhile, the structure of the title compound was not only certified by MS, 1 H NMR, FT-IR, and 13 C NMR spectroscopy, but the compound's single crystal was measured by X-ray diffraction. The optimized molecular crystal structure was ulteriorly determined using density functional theory (DFT), and it was compared with the value of X-ray diffraction. Furthermore, through more deeply studies by means of the molecular electrostatic potential and frontier molecular orbitals (FMOs) of compound 1, more physicochemical properties were investigated.